When is a lie not a lie? When it’s divergent : Examining lies and deceptive responses in a police interview - Carter, Elisabeth (Language and Law / Linguagem e Direito, 2017)
Using UK police interviews as data, this empirical work seeks to explore and explain the interactional phenomena that accompany, distinguish, and are drawn upon by suspects in performing deceptive talk. It explores the effects of the myriad and often conflicting interactional requirements of turntaking, preference organisation and conversational maxims on the suspect’s talk, alongside the practical interactional choices of a suspect attempting to avoid revealing his guilt. This paper reveals a close link between the oXcer’s and suspect’s interaction and the patterned organisation of an assortment of divergent utterances produced in response to probing questions that follow a lie. The Vndings expose a hierarchical interactional order that explains the diverse and conWicting accounts of cues to deception in this Veld, suggesting that interactional phenomena are systematically enlisted in the orientating to, and the violation of interactional organisation which enables the suspect to produce utterances that protect his position, and can also be directed towards the performance of wider objectives such as reinforcing a claim of innocence or supporting a version of events.